"They Seem to be Able to Read Your Mind." An Interview Study to Identify the Cognitive Non-Technical Skills of Anaesthetic Assistants. Issue 9 (September 2015) - Rutherford, Js; Flin, R; Mitchell, L
The aim of this study was to identify the cognitive non-technical skills (i.e. situation awareness and decision making) used by anaesthetic assistants, as part of the development of a specialty-specific behavioural rating system for anaesthetic assistants. Semi-structured interviews were conducted with anaesthetic assistants (n=22), anaesthetic consultants (n=11) and trainee anaesthetists (n=12) in Scotland. The interviews were transcribed and thematically analysed. All 45 participants described the presence or failure of situation awareness (i.e. gathering information, its comprehension and anticipation) in 713 phrases. Decision making (i.e. considering options, selecting actions and reviewing decisions) by the anaesthetic assistants was reported much less frequently – only 34 participants described 89 phrases. Situation awareness is a key non-technical skill used by anaesthetic assistants, however decision making was less commonly described as required by anaesthetic assistants. This provides qualitative data to support the development of a non-technical skills taxonomy for anaesthetic assistants.